Modelagem hidrológica da bacia do Rio Jucu sob diferentes cenários de cobertura florestal - Pimentel, Stefania Marques (2017)
Water is a natural resource of public domain and indispensable for the maintenance of life on the planet. There are many discussions about the effect of forest cover and land use on the "production" of water. he hydrological studies contribute to the understanding of the water cycle, especially in relation to the water availability, characterized by the flow. The objective of this research was to analyze the impact of forest cover on flow behavior in the Jucu river basin, Espírito Santo, through hydrological modeling, using the Soil and Water Assessment Tool (SWAT) model. The efficiency of the simulation of the daily and monthly flows was evaluated through the static indexes: Nash and Sutcliffe efficiency coefficient (NS); Coefficient of determination (R2); Normalized standard error (RSR) and percentage of trend (PBIAS) that indicated satisfactory performance in the calibration and validation phases of the model. After calibration and validation of the model, simulations of alternative land use scenarios of the Jucu river basin were carried out. In order to verify the influence of the geographic position of the reforestation on the flows, the scenarios were constructed in two different ways: a) "random" approach (AA), in which no matter the location of the reforested areas; B) "defined" approach (AD), in which are defined exactly in which geographical positions will be the reforestation (areas under macega and, or, permanent preservation areas). The results of the AA showed a low expressive tendency of reduction of simulated flows, as the forest area increases, demonstrating that the geographical position in which the land use change will be carried out is more important for the behavior of the minimum flows than for the Flow rates.